2021
DOI: 10.1155/2021/6674505
|View full text |Cite
|
Sign up to set email alerts
|

Choroidal Detachment after XEN Gel Stent Implantation

Abstract: Background. The purpose of this study is to estimate the incidence of choroidal detachment (CD) after XEN gel stent implant surgery and to evaluate the associated factors. Methods. We reviewed the clinical charts of 126 patients who underwent XEN implantation between March 1, 2016, and December 31, 2018 at the University Eye Clinic of Genoa. Ocular, demographics, and perioperative factor were registered and analysed. Univariate and multivariate logistic analysis were performed to investigate factors associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…One study focusing on Xen45 Implants in particular found that significant risk factors predisposing for choroidal detachment include increased age, a higher number of preoperative IOP-lowering drugs, and lower IOP within 1 week postoperatively. 15 These major risk factors were seen in our case as well.…”
Section: Discussionsupporting
confidence: 76%
“…One study focusing on Xen45 Implants in particular found that significant risk factors predisposing for choroidal detachment include increased age, a higher number of preoperative IOP-lowering drugs, and lower IOP within 1 week postoperatively. 15 These major risk factors were seen in our case as well.…”
Section: Discussionsupporting
confidence: 76%
“…The assessment of factors associated with the occurrence of this complication was reported in a previous study. 17 In the postoperative management analysis (table 4), the number of postoperative visits showed a marginally significant difference between the two groups. The trabeculectomy group showed fewer postoperative visits over 24 months period, while the difference between the two groups lost significance at 12 months.…”
Section: Discussionmentioning
confidence: 92%
“…The assessment of factors associated with the occurrence of this complication was reported in a previous study. 17 …”
Section: Discussionmentioning
confidence: 99%
“…According to recent studies, three main risk factors predispose patients to CD after XEN45 implantation: (i) older age, (ii) excess preoperative medications to lower IOP, and (iii) low IOP within one week after surgery [ 14 ]. Importantly, these risk factors were present in the clinical case reported here, in which persistent serous CD with visual loss occurred in both eyes after XEN45 implantation.…”
Section: Discussionmentioning
confidence: 99%